GOD SERVANTS' KNOWLEDGE AND STIGMA OF TUBERCULOSIS IN KUPANG INDONESIA - Manurung, Imelda Februati Ester; Ruliati, Luh Putu; Ndun, Helga J. N; Baun, Aminah H; Lele, Yumiati Ke; Wahyuni, Chatarina U (YCAB Publisher & IAKMI SULTRA, 2018)
Background: Knowledge and stigma are the factors that determine the success of TB control. The people of East Nusa Tenggara still rely heavily on the support of God's servants in addressing health issues. God's servant is someone who is believed to have the gift of healing through prayer to the Lord Jesus. Aim: This study aimed to reveal God's servants' knowledge on and stigma to TB.Methods: This study is a descriptive quantitative study, in which the research aims to perceive God's servants' knowledge and stigma to TB in 2 community health centers with the most TB cases in Kupang. The population of the study was God's servants in three areas of coverage of community health centers with the most TB cases. The sample of the study was the entire population (Total sampling) as many as 120 people. Data were collected through questionnaires and using mid-point score.Results: The results showed that the knowledge related to transmission, treatment, and prevention of Tuberculosis was low, amounted to 76%, similar to the stigma to TB that was amounted to 58%. God's servants still held the stigma that TB is a curse and disgraceful disease and they were unwilling to share with tuberculosis patients.Conclusion: God's servants' knowledge related to TB is low. As for stigma, even though mostly is low, there are still many God's servants who give stigma to TB disease. Since God's servant is a potential figure believed by some people to have the gift of healing, their knowledge and stigma needs to be improved in order to provide true information and support for TB patients.